(untitled) (SciELO Preprints, 2020)
The severe acute respiratory syndrome of the new coronavirus, SARS CoV-2, which became a pandemic, was first reported in Wuhan, Hubei, China in December 2019. It can cause mild symptoms, but in some cases it can cause serious complications, leading to death. The disease spreads through aerosol droplets and has estimated incubation period between 2 and 14 days (a period in which the patient has high potential to infect other people). Endodontists have high risk of exposure to COVID-19 when compared to other health professionals, since most of the work involves the generation of aerosols and care for patients in emergency situations, such as symptomatic irreversible pulpitis, symptomatic apical periodontitis, acute apical abscess and traumatic dental injuries, is imperative. Thus, this critical review addresses considerations about endodontic care in times of pandemic, whose emergencies imply real need for treatment, as well as the care that must be adopted in order to minimize risks for both professionals and patients who seek the resolution of their clinical pain conditions.